ST-Segment Elevation Associated with Mobitz II Atrioventricular Block During Transseptal Puncture for Atrial Fibrillation Ablation - Damasco do Vale, Paula; Teixeira Martins e Silva, Lívia; Macedo da Rocha, Jairo; Septimio Margalho, Carla; de Almeida Maia, Henrique César (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Pulmonary veins electrical isolation as an invasive treatment of atrial fibrillation has been widely used in electrophysiology laboratories. This case report presents a rare and transient complication, during transseptal puncture for atrial fibrillation ablation. ST-segment elevation, hypotension and bradyarrhythmia related to catheterization were observed despite cineangiocoronariography without obstructive lesions. Clinical stability was achieved after administration of intravenous atropine and saline solution. It is speculated that the phenomenon is attributed to an increased vagal tone after the mechanical effect of transseptal puncture in the interatrial vagal network. The procedure was completed despite the phenomenon.